(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The integration of Sustainable Development Goals (SDGs) into life sciences education is essential for addressing the global challenges of food security, environmental sustainability, and climate change. This paper examines role of life sciences teaching in addressing key SDGs, highlighting challenges and opportunities within the NEP’s framework and proposing strategies for nurturing professionals capable of tackling global sustainability challenges. Life sciences education is crucial for addressing SDGs related to climate action, biodiversity, food security, and sustainable agriculture. By embedding sustainability principles in curricula, educators empower students to contribute to these goals through research and conservation. Successful integration depends on revamping curricula, adopting problem-based learning, and providing faculty development. NEP 2020’s emphasis on interdisciplinary education provides a platform to integrate biology, ecology, agronomy, and environmental sciences, fostering deeper understanding. Opportunities include flexible curriculum design for innovative teaching methods like field studies and green technology demonstrations. Challenges such as resource limitations and faculty shortages require collaborative efforts among academia, government, NGOs, and industry. In conclusion, integrating sustainability into Life science education under the NEP can cultivate environmentally conscious citizens and contribute to achieving the SDGs. Educators must address challenges and seize opportunities to foster a generation committed to sustainability.